Affect of Early Life Oxygen Exposure on Proper Lung Development and Response to Respiratory Viral Infections - Domm, William; Misra, Ravi S.; O’Reilly, Michael A. (Frontiers in Medicine, 2015)
Children born preterm often exhibit reduced lung function and increased severity of response to respiratory viruses, suggesting that premature birth has compromised proper development of the respiratory epithelium and innate immune defenses. Increasing evidence suggests that premature birth promotes aberrant lung development likely due to the neonatal oxygen transition occurring before pulmonary development has matured. Given that preterm infants are born at a point of time where their immune system is also still developing, early-life oxygen exposure may also be disrupting proper development of innate immunity. Here we review current literature in hopes of stimulating research that enhances understanding of how the oxygen environment at birth influences lung development and host defense. This knowledge may help identify those children at risk for disease and ideally culminate in the development of novel therapies that improve their health.